2022
DOI: 10.3390/clockssleep4010004
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sectional Study of the Community Self-Reported Risk of Obstructive Sleep Apnoea (OSA) and Awareness in Thessaly, Greece

Abstract: The purpose of this study was to investigate the self-reported risk of obstructive sleep apnea syndrome (OSAS) in the municipality of Thessaly, Greece, and the level of awareness of both the disease and its diagnosis. Inhabitants of Thessaly (254 total; 84 men and 170 women) were studied by means of questionnaires via a telephone-randomized survey. This comprised: (a) the Berlin questionnaire for evaluation of OSAS risk; (b) the evaluation of daytime sleepiness by the Epworth Sleepiness Scale; and (c) demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The self-reported prevalence of OSA was found to be 27.09%, similar to what was found in two previous reports by our research group that were performed as telephone surveys and assessed self-reported OSA community prevalence [ 1 , 3 ]. The first study was performed in the insular population of 41 Greek islands (other than the Sporades insular complex) of the Aegean and Ionian Pelagos with a self-reported prevalence of 27.29%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The self-reported prevalence of OSA was found to be 27.09%, similar to what was found in two previous reports by our research group that were performed as telephone surveys and assessed self-reported OSA community prevalence [ 1 , 3 ]. The first study was performed in the insular population of 41 Greek islands (other than the Sporades insular complex) of the Aegean and Ionian Pelagos with a self-reported prevalence of 27.29%.…”
Section: Discussionsupporting
confidence: 88%
“…According to the latest study regarding smoking prevalence in Greece performed in 2020, 28% of the population are active smokers, so the numbers remain very high [ 17 ]. In Central Greece and Thessaly, the prevalence is even higher, ranging from 32.4 to 35.78% [ 1 , 3 , 18 ]. These numbers are very alarming since smoking is the cause of COPD, of which the burden in Greece is significant [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This deters the establishment and application of population-specific health promotion strategies. Two recent studies by our research group highlighted the fact that insular smoking prevalence is substantially higher than the already-high national prevalence [ 9 , 10 ]. Moreover, in the recently published first report of the Alonissos Study, it was shown that there is a high prevalence of COPD and OSAS on Alonissos island, highlighting the need for primary healthcare awareness in this non-profit-line Greek island [ 1 ].…”
Section: Introductionmentioning
confidence: 99%